Uma leitura dialética do romance Água de barrela de Eliana Alves Cruz - Lima, Cátia de Jesus (Universidade Federal de São Carlos, 2025)
This dissertation presents an analysis of Água de Barrela (2018), written by Rio de Janeiro author Eliana Alves Cruz. By focusing on the marital relationships and the roles of the female characters at the center of the plot, the study aims to problematize and understand Black patriarchy and the marginalized male profiles depicted in the narrative. In this regard, analyzing the characteristics and actions of these characters within both familial and social contexts is essential to reveal how the masculine antagonism that emerged in the post-abolition period—when descendants of Africans were forced to work under conditions akin to slavery to survive, or, unable to endure this new reality, turned to idleness and/or criminality—is deeply connected to capitalism and patriarchy. These structures prevent Black men from having the same opportunities as white men. To that end, the novel is examined through the method of successive readings proposed by Roberto Schwarz in A poesia envenenada de Dom Casmurro (2006), in order to show that, beyond the protagonists’ personal experiences and their overcoming of hardships, there exists a broader historical narrative. This larger story unfolds in parallel with the maturation of capitalism in Brazil, particularly involving the proletarian class of Salvador. Therefore, a more in-depth analysis of the work proves relevant in bringing this working-class group to the forefront of the narrative—especially the causes that led to the 1919 General Strike, a significant event that allows the repositioning of male characters, previously seen as secondary, into active subjects engaged in the sociopolitical processes of the time. This shift challenges the historically constructed stereotype of Black men as delinquents and reaffirms their role in the Brazilian labor struggle within the Bahian context.
A dialectical reading of the novel Água de barrela by Eliana Alves Cruz
Keywords: Água de Barrela; Eliana Alves Cruz; Leitura política; Literatura contemporânea; Personagens masculinos; Political reading; Contemporary literature; Male characters; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA BRASILEIRA; 10. Redução das Desigualdades